2017
DOI: 10.1038/srep43756
|View full text |Cite
|
Sign up to set email alerts
|

Transfer free graphene growth on SiO2 substrate at 250 °C

Abstract: Low-temperature growth, as well as the transfer free growth on substrates, is the major concern of graphene research for its practical applications. Here we propose a simple method to achieve the transfer free graphene growth on SiO2 covered Si (SiO2/Si) substrate at 250 °C based on a solid-liquid-solid reaction. The key to this approach is the catalyst metal, which is not popular for graphene growth by chemical vapor deposition. A catalyst metal film of 500 nm thick was deposited onto an amorphous C (50 nm th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…In fact, it was demonstrated very recently that graphene can form even at the temperature as low as 250 C using Sn, a low melting point (MP) metal catalyst by solid-liquid-solid phase reaction. 27 Carbon atoms in molten metal would meet this condition. MP of bulk In is 156.6 C, and it is also well-known that the smaller the particle size, the lower the MP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it was demonstrated very recently that graphene can form even at the temperature as low as 250 C using Sn, a low melting point (MP) metal catalyst by solid-liquid-solid phase reaction. 27 Carbon atoms in molten metal would meet this condition. MP of bulk In is 156.6 C, and it is also well-known that the smaller the particle size, the lower the MP.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24] They were featured by metal nanoparticles dispersed in amorphous CNF matrix and transferred into graphene and CNT only aer the electron current ow (resistive Joule heating) or heating in vacuum. 23,25,26 Very recently, Sn, which is not popular as a catalyst for the CVD graphene growth, was demonstrated to be promising as a novel catalyst for the low-temperature transfer-free graphene growth (at 250 C) 27 directly on SiO 2 substrate by our group. This inspired us for the further selection of suitable metals to be included into ion-induced CNFs for synthesizing highly crystalline graphene at lower temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The diffusion and segregation processes of carbon differ from those at high temperatures and rely on the concentration gradients. Even in recent work reporting conversion of amorphous carbon to graphene at 250 °C by using tin as catalyst [21], only discontinuous graphene flakes were formed. In particular, Weatherup et al reported that graphene with domain sizes of > 220 μm² could grow on polycrystalline Ni-Au catalyst films at 450-600 °C, indicating the possibility of large-area graphene growth [17].…”
Section: Introductionmentioning
confidence: 94%
“…Co has the highest solubility for carbon and Fe is cheaper than Ni and Co. Today, nickel and copper are receiving the most attention as substrate materials for graphene growth because they are inexpensive and are standard materials for electronic applications. Other metals and alloys including tin (Vishwakarma et al, 2017 ) and Ni-Cu alloy (Abd Elhamid A. M. et al, 2017 ) have also been used for graphene synthesis.…”
Section: Pld Graphene Growth Using Metal Catalystmentioning
confidence: 99%
“…Vishwakarma et al ( 2017 ) reported an attempt to grow multi-layer graphene at a low temperature (250°C) using another metal catalyst, tin (Sn) and the PLD technique. In fact, this is the first attempt to grow PLD graphene using tin as catalyst.…”
Section: Pld Graphene Growth Using Metal Catalystmentioning
confidence: 99%